2015
DOI: 10.3406/revec.2015.1798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodic defoliations by Thaumetopoea pityocampa Schiff. on radial growth in cedar woodland in Chréa, Algeria

Abstract: Effet des défoliations périodiques par Thaumetopoea pityocampa Schiff. sur la croissance radiale des cèdres du Chréa, Algérie. La forêt emblématique de cèdres (Cedrus atlantica Manetti) du parc national de Chréa, 40 km au sud-ouest d’Alger, est attaquée par la Processionnaire du pin (Thaumetopoea pityocampa Schiff.). Nous avons étudié l’impact des pullulations successives de cette processionnaire entre 1980 et 2009 sur la croissance des cèdres pour voir si un éventuel effet cumulatif pourrait affecter la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Similar results (1.5 ± 0.23 tents/tree) were found in Bordj-Bou-Arreridj region (Northeastern Algeria) (Ziouche et al 2017). A higher level of population density of T. pityocampa was observed in the National Park of Chrea (Northen Algeria) (5.3-15.2 tents/tree for the years 1991-2014) (Sebti and Chakali 2014;Sbabdji et al 2015). In several European countries, repeated outbreaks of T. pityocampa have been recorded (Arnaldo et al 2010;Sbabdji and Kadik 2011;Salman et al 2016;Bourougaaoui et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results (1.5 ± 0.23 tents/tree) were found in Bordj-Bou-Arreridj region (Northeastern Algeria) (Ziouche et al 2017). A higher level of population density of T. pityocampa was observed in the National Park of Chrea (Northen Algeria) (5.3-15.2 tents/tree for the years 1991-2014) (Sebti and Chakali 2014;Sbabdji et al 2015). In several European countries, repeated outbreaks of T. pityocampa have been recorded (Arnaldo et al 2010;Sbabdji and Kadik 2011;Salman et al 2016;Bourougaaoui et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a severe attack by Thaumetopoea pityocampa Schiff. on C. atlantica in Chreá National Park, Algeria were studied by Sbabdji et al (2015). They found that the infection resulted in up to a 50% growth decline after complete defoliation.…”
Section: Algeriamentioning
confidence: 99%